The Role of PPAR in Liver Cirrhosis: An Update Review - Sholihah, Mentari Maratus; Pramana, Triyanta Yuli; Hanif, Muhammad Ifham (Gema Lingkungan Kesehatan, 2025)
Liver cirrhosis is the final stage of various chronic liver diseases characterized by fibrosis and nodule formation in the liver. The pathophysiology of liver cirrhosis involves a complex process, in which the role of peroxisome proliferator-activated receptors (PPAR) is very important. PPARα, which is mainly expressed in the liver, plays an important role in the regulation of hepatic lipid metabolism. In cirrhosis, PPARα expression is decreased, resulting in impaired fatty acid oxidation and increased lipogenesis. This contributes to the accumulation of fat in the liver, which is one of the characteristics of NAFLD that can progress to cirrhosis. PPARγ, although better known for its role in adipose tissue, also has important functions in the liver. In cirrhosis, PPARγ plays a role in inhibiting the activation and proliferation of HSCs, and modulating macrophage polarization. PPARγ activation can reduce liver inflammation and fibrosis, and increase insulin sensitivity. Recent studies have shown that PPARγ agonists can improve steatosis, reduce inflammation, and significantly improve the response to hepatitis viruses. PPARδ, which is widely expressed in various tissues including the liver, plays a role in lipid metabolism and liver inflammation. Moreover PPARs role in viral hepatitis induced liver chirrosis is still remain controversial. Although research on PPARδ in the context of liver cirrhosis is still limited, several studies have shown its potential anti-fibrotic effects. Thus, a deeper understanding of the role of PPARs in the pathophysiology of liver cirrhosis opens up new opportunities for the development of more effective therapies to treat this chronic liver disease.